Study the Value of Togetherness and Gotong Royong (Team Work) Of Flying Duce Race in Limapuluh Kota Regency - Febrysa Varensya; Hambali Hambali; Hariyanti Hariyanti (Universitas of Muhammadiyah Makassar, 2022)
This research is based on the trend of folk traditions in the people of West Sumatra. One of them is a tradition in the form of a competition that uses livestock such as cows, buffaloes, and ducks were in its implementation the community blends from several Luak Limapuluh (Limapuluh Kota Regency and Payakumbuh) West Sumatra Province. This study intends to explain the values of togetherness and gotong royong (team work) in the tradition of Flying Duck Race in the Limapuluh Kota Regency. The formulation of the problem in this study is how the values of togetherness and gotong royong (team work) in the tradition of Flying Duck Race of Limapuluh Kota Regency. The purpose of this study is to analyze how the values of togetherness and mutual cooperation in the tradition of Flying Duck Race in Limapuluh Kota regency. The data collection techniques in this study are observation, interviews, and documentation. The informants in this study consisted of 9 (nine) people, namely the Chairman of the Nagari Traditional Density as well as the head of porti, the Tourism Office for Sports and Culture of Limapuluh Kota Regency, the Chairman of the Luak Reinbond the Chief Executive, the Competition Participants, and the community. Data analysis techniques use qualitative methods with a sociological study approach. The results in this study explain that in the tradition of Flying Duck Race there are values of togetherness in the form of humility, service and mutual cooperation has values in the form of unity, voluntary, kinship, help which are reflected when the implementation starts from the pre-implementation stage to the post-implementation or evaluation stage where the tradition is always maintained in the life of the community.